Mango Peel Pectin: Recovery, Functionality and Sustainable Uses - Malaiporn Wongkaew (MDPI AG, 2021)
Concerns regarding the overconsumption of natural resources has provoked the recovery of biopolymers from food processing biomass. Furthermore, the current market opportunity for pectin in other areas has increased, necessitating the search for alternative pectin resources. This is also a step towards the sustainable and circular green economy. Mango peel is the byproduct of agro-processing and has been used for high value-added components such as polysaccharide biopolymers. Pectin derived from the peel is yet to be exploited to its greatest extent, particularly in terms of its separation and physiochemical properties, which limit its applicability to dietary fiber in culinary applications. The functionality of the mango peel pectin (MPP) strongly depends on the molecular size and degree of esterification which highlight the importance of isolation and characterisation of pectin from this novel resource. This article therefore provides a useful overview of mango peel as a potential biomaterial for the recovery of MPP. Different extraction techniques and the integrated recovery were also discussed. The utilisation of MPP in different industrial schemes are also detailed out from different perspectives such as the pharmaceutical and biotechnology industries. This review convincingly expresses the significance of MPP, providing a sustainable opportunity for food and pharmaceutical development.